2022
DOI: 10.1186/s42836-022-00142-7
|View full text |Cite
|
Sign up to set email alerts
|

Patients at a high risk of PJI: Can we reduce the incidence of infection using dual antibiotic-loaded bone cement?

Abstract: Prosthetic joint infection (PJI) is one of the most devastating complications of orthopedic surgery. However, not all patients are equally at the risk of severe infection. The incidences of PJI vary with the host and surgery-related risk factors. It is now generally accepted that some important medical comorbidities may predispose the patients to a high risk of PJI. Time-consuming and invasive surgical procedures, such as revision arthroplasties, are also associated with a high incidence of PJI, presumably due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Third, recent studies are controversial on whether antimicrobial-containing cement is effective in preventing PJI. [34,35] However, this method may prevent PJI long-term by reducing dead space. Despite these limitations, this method could be useful as an infection control measure.…”
Section: Discussionmentioning
confidence: 99%
“…Third, recent studies are controversial on whether antimicrobial-containing cement is effective in preventing PJI. [34,35] However, this method may prevent PJI long-term by reducing dead space. Despite these limitations, this method could be useful as an infection control measure.…”
Section: Discussionmentioning
confidence: 99%
“…They highlighted the need for careful patient selection and appropriate antibiotic choice to maximize benefits and minimize risks. Berberich et al [ 18 ] reviewed the potential of dual antibiotic-loaded bone cement (ALBC) in the prevention of PJI in high-risk patients. Studies indicated that the local delivery of antibiotics via bone cement could provide enhanced and sustained antimicrobial effects, thereby lowering the incidence of PJI.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, after the evidence that antibiotic-loaded cement lowers infection rates and does not contribute to the exacerbation of antibiotic resistance 18 , it has become widely used as a prophylactic measure. There are even proposals for using dual antibiotic-loaded bone cement, which can be synergistically efficacious 19 .…”
Section: Introductionmentioning
confidence: 99%